2020
DOI: 10.3390/ijms21061967
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 Up-Regulate Chondrogenic Differentiation by Transform Growth Factor Receptors

Abstract: Mesenchymal stem cells, also known as multipotent stromal progenitor cells, can differentiate into cells of mesodermal lineage. Gangliosides are sialic acid-conjugated glycosphingolipids that are believed to regulate cell differentiation and several signaling molecules. These molecules are localized in glycosphingolipid-enriched microdomains on the cell surface and are regulated by glycosphingolipid composition. Transforming growth factor-beta (TGF-β) signaling plays a critical role in chondrogenic differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…Hence, we propose several GM3 ganglioside (molecular) species as potential markers for adipogenic differentiation ( Figure 7 ). Regarding chondrogenic differentiation, our study does not confirm former results(Ryu et al, 2020). Instead of increased expression of GM3 and GD3, we found ganglioside classes GM4 and GT3 significantly upregulated in the chondrogenic lineage compared to native MSCs.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, we propose several GM3 ganglioside (molecular) species as potential markers for adipogenic differentiation ( Figure 7 ). Regarding chondrogenic differentiation, our study does not confirm former results(Ryu et al, 2020). Instead of increased expression of GM3 and GD3, we found ganglioside classes GM4 and GT3 significantly upregulated in the chondrogenic lineage compared to native MSCs.…”
Section: Discussioncontrasting
confidence: 99%
“…After chondrogenic differentiation of both BMSCs and iPS-MSC like cells, the expression of GM3 increased temporarily. Ryu et al reported that GM3 and GD3 were expressed after chondrogenic differentiation and GM3 enhanced TGF-β signaling via SMAD 2/3 [32]. These results might suggest that BMSCs and iPS-MSCs differentiated into chondrocytes.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, after the chondrogenic differentiation of BM-MSCs, the expression of GM3 temporarily increases. Ryu et al reported that GM3 and GD3 are expressed after the chondrogenic differentiation and GM3 enhanced transforming growth factor-beta (TGF-β) signaling via SMAD 2/3 [ 37 ]. However, GM3 levels significantly decreased, whereas GM1, GD3, and GD1a levels increased during further differentiation into chondrocytes [ 87 ].…”
Section: Role Of Gangliosides During Multilineage Differentiation Of ...mentioning
confidence: 99%
“…GGs have important biological characteristics and functions [ 34 ], including regulation of cell proliferation, adhesion, migration, apoptosis, cell-cell interactions, cell differentiation [ 35 , 36 , 37 ], and interaction with proteins [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%